Hyperglycemia induces mixed M1/M2 cytokine profile in primary human monocyte-derived macrophages - Moganti, Kondaiah; Li, Feng; Schmuttermaier, Christina; Riemann, Sarah; Klüter, Harald; Kzhyshkowska, Julia (Immunobiology, 2017)
Hyperglycaemia is a key factor in diabetic pathology. Macrophages are essential regulators of inflammation which can be classified into two major vectors of polarisation: classically activated macrophages (M1) and alternatively activated macrophages (M2). Both types of macrophages play a role in diabetes, where M1 and M2-produced cytokines can have detrimental effects in development of diabetes-associated inflammation and diabetic vascular complications. However, the effect of hyperglycaemia on differentiation and programming of primary human macrophages was not systematically studied. We established a unique model to assess the influence of hyperglycaemia on M1 and M2 differentiation based on primary human monocyte-derived macrophages. The effects of hyperglycaemia on the gene expression and secretion of prototype M1 cytokines TNF-alpha and IL-1beta, and prototype M2 cytokines IL-1Ra and CCL18 were quantified by RT-PCR and ELISA. Hyperglycaemia stimulated production of TNF-alpha, IL-1beta and IL-1Ra during macrophage differentiation. The effect of hyperglycaemia on TNF-alpha was acute, while the stimulating effect on IL-1beta and IL-1Ra was constitutive. Expression of CCL18 was supressed in M2 macrophages by hyperglycaemia. However the secreted levels remained to be biologically significant. Our data indicate that hyperglycaemia itself, without additional metabolic factors induces mixed M1/M2 cytokine profile that can support of diabetes-associated inflammation and development of vascular complications.